2019
DOI: 10.3389/fimmu.2019.00873
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of miR-181a-5p and miR-155-5p Plasmatic Expression as Prognostic Biomarkers for Acute and Subclinical Rejection in de novo Adult Liver Transplant Recipients

Abstract: Background and Aims: News strategies for the accurate assessment of the state of immunosuppression (IS) in liver transplant recipients are needed to prevent rejection and minimize drug-related side effects. miRNAs can potentially be used as diagnostic or prognostic biomarkers in transplant patients. This study evaluated the capacity of a plasmatic miRNA panel (miR-155-5p, miR-122-5p, miR-181a-5p, and miR148-3p) as an early non-invasive prognostic and diagnostic biomarker for T cell-mediated acute re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 37 publications
1
31
0
Order By: Relevance
“…Statistical differences between groups were assessed with the Mann‐Whitney test, and correlations between NFAT‐RGE, intralymphocytary cytokines and clinical events were assessed with Spearman's Rho test. We used a receiver operating characteristic (ROC) curve analysis to define the optimal cut‐off values for differentiating between patient groups with and without TCMAR or SCR following the same criteria that we applied in our previous publication . All analyses were performed using SPSS 23.0 software (SPSS, Inc), and all data are presented as the median ± standard deviation (SD).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical differences between groups were assessed with the Mann‐Whitney test, and correlations between NFAT‐RGE, intralymphocytary cytokines and clinical events were assessed with Spearman's Rho test. We used a receiver operating characteristic (ROC) curve analysis to define the optimal cut‐off values for differentiating between patient groups with and without TCMAR or SCR following the same criteria that we applied in our previous publication . All analyses were performed using SPSS 23.0 software (SPSS, Inc), and all data are presented as the median ± standard deviation (SD).…”
Section: Methodsmentioning
confidence: 99%
“…Triple therapy with CNi with reduced target trough levels (5‐8 ng/mL for Tac and 75‐150 ng/mL for CsA) with mycophenolate mofetil (MMF), corticosteroids and induction therapy with a single dose of basiliximab was given to Child‐Pugh B or C patients, retransplanted patients and to those transplanted because of acute liver failure. In both cases, the corticosteroids were tapered and withdrawn earlier than 6 months after LT …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(12) miRNAs can be detected in plasma and have been proposed as potential biomarkers under certain conditions. (13) In LT, although previous studies have suggested the differential plasmatic expression of certain miRNAs both before and during TCMR, (14)(15)(16) the evidence regarding their clinical use is still scarce. Thus, we aimed to assess the performance of a panel of 4 miR-NAs (155-5p, 122-5p, 181a-5p, and 148-3p) in diagnosing TCMR in a prospective cohort of LT patients with GD who underwent LB and to compare its diagnostic accuracy with that of other noninvasive tests.…”
mentioning
confidence: 99%
“…miRNAs, which are ~20–22 nucleotide single-stranded RNA species, and play a central role in the regulation of protein-coding genes, are also emerging as robust biomarkers for assessing allograft status. Millán et al have reported that plasma miRNAs can serve as early non-invasive prognostic and diagnostic biomarkers for T-cell mediated acute rejection in LT recipients, that is, miR-155-5p regulates the differentiation of CD4 + T cells into Th cells and IFN-γ production in human T and NK cells, and miR-181a levels modulate T cell receptor sensitivity and intensity of signaling ( 140 ). Hence, the plasma levels of miR-155-5p and miR-181a-5p after LT potentially help identify patients for IS minimization.…”
Section: Outlook On Employing Snps and Mirnas For Tolerancementioning
confidence: 99%